Tools of Deception: Media Coverage of Student Protests in Tanzania (Nordic Journal of African Studies, 2000)
It is widely recognized that news, like other forms of discourse, is not a neutral representation of facts (van Dikj 1988, 1992, 1995; Fairclough 1995a, 1995b; Fowler 1987; McLeod and Hertog 1992; Downing 1990). Writers, editors, and presenters of news select, interpret and present events from particular ideological positions. They not only present selected facts according to their orientation, but also construct reality in a manner consistent with their underlying ideologies. News reports, therefore, impose a world view of the editors, writers, and presenters and their value systems.